Liparis volcanica (Orchidaceae), una especie nueva del occidente de México - Gonzalez Tamayo, Roberto; Zamudio, Sergio (Instituto de Ecología, A.C., 1993)
Liparis volcanica from Nayarit, Jalisco and Michoacan states, is proposed as a new species. It is compared with Liparis greenwoodiana Espejo, its most close ally. The most important differences between these taxa are found in the form of the lip.